Strategies for building institutional repositories: a case study of content recruitment in Malaysian higher learning institutions - Raudhah Osman,; Abrizah A.,; Yanti Idaya A.M.K., (Malaysian Journal of Library and Information Science, 2023)
Various strategies have been developed to ensure the success of the critical and challenging process of recruiting content for institutional repositories. This article presents an in-depth exploration of content recruitment strategies used by three Malaysian higher learning institutions in their institutional repositories. Through interviews with nine repository librarians, the study investigates the various methods used to acquire content, including mediated deposit, self-archiving, and promotion activities. The study reveals that setting up content deposit as a quality objective and key performance indicator (KPI) is a new and effective strategy used among the three case studies. The findings provide valuable insights into the approaches taken by these institutions to recruit content and offer practical guidelines for academic librarians in general. This study contributes to the growing body of knowledge on institutional repository management, highlighting the importance of implementing effective content recruitment strategies to ensure the success and sustainability of these repositories.